Evaluation of calcium alginate hydrogel for suprachoroidal buckling in a rabbit model—a pilot study on efficacy and biocompatibility - Xingyu Xiao; Xingyu Xiao; Xingyu Xiao; Yan Zhou; Yan Zhou; Yan Zhou; Shiqun Lin; Shiqun Lin; Shiqun Lin; Huan Chen; Huan Chen; Huan Chen; et al. (Frontiers in Medicine, 2025)
PurposeThis study aimed to evaluate the therapeutic efficacy, safety, and biocompatibility of calcium alginate hydrogel in suprachoroidal buckling procedures performed on rabbit eyes.MethodsA total of 21 healthy New Zealand White rabbits underwent surgery, during which calcium alginate hydrogel was injected into the suprachoroidal space of one eye. Monthly ophthalmic examinations were performed for 3 months following the procedure. The assessments included external eye and fundus examinations, color fundus imaging, and optical coherence tomography. At the end of the observation period, both eyes from each rabbit were enucleated and subjected to histopathological evaluation.ResultsThe surgery was successfully performed on 21 eyes, with a success rate of 80.95% (17/21). A total of 17 eyes showed favorable postoperative outcomes and no complications. The average maximum dome height is 2,470.42 ± 876.11 μm on the day of operation and 1,585.97 ± 351.93 μm 3 months postoperatively, with the average difference of 866.37 ± 592.94 μm. A total of four eyes experienced inadvertent perforations of both the choroid and retina, leading to vitreous and suprachoroidal hemorrhages. Histological evaluation confirmed the persistent presence of a suprachoroidal indentation in the treated eyes of the 17 rabbits without complications, with no observable abnormalities detected in the lenses or retinas.ConclusionCalcium alginate hydrogel proved to be a safe and effective material for suprachoroidal buckling in rabbits, exhibiting excellent biocompatibility.